Synopsis of the Compositae Giseke of La Pampa, Argentina (Semiárida, 2020)
In this work (203 taxons are recorded, belonging to 194 species, 93 genera, 13 tribes and 2 subfamilies. Keys for tribes, genera and species are attached. The valid name, synonyms and popular name of each taxon, are given; also the bibliography of the first c1tation, iconography, distribution and frequency in La Pampa and a selected examined herbarium specimen are included. A summary table with origin, numbers of endemic taxons and number of tribes, genera, species and taxons is attached.
Keywords: compositae; taxons; Sinopsis; Provincia de La Pampa